2023
DOI: 10.3390/pharmaceutics15092178
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of Phytosomes Containing Callistemon citrinus Leaf Extract: A Preclinical Approach for the Treatment of Obesity in a Rodent Model

Luis Gerardo Ortega-Pérez,
Luis Alberto Ayala-Ruiz,
Oliver Rafid Magaña-Rodríguez
et al.

Abstract: Callistemon citrinus has several biological effects; it is anti-inflammatory, anti-obesogenic, antioxidant, hepatoprotection, and chemoprotective. Its bioactive compounds include terpenoids, phenolic acids, and flavonoids which have low oral bioavailability and absorption. This study aimed at developing phytosomes of C. citrinus to improve oral bioavailability and absorption. Phytosomes were formulated with soybean phosphatidylcholine and C. citrinus leaf extract using the thin layer sonication method. Phytoso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…In addition, both products reduced excessive weight in the obese rats. The administration of C. citrinus phytosomes, even in low doses, further reduced the adiposity index and TG levels in obese rats, compared to the unformulated extract [200].…”
Section: Preclinical Studiesmentioning
confidence: 89%
See 2 more Smart Citations
“…In addition, both products reduced excessive weight in the obese rats. The administration of C. citrinus phytosomes, even in low doses, further reduced the adiposity index and TG levels in obese rats, compared to the unformulated extract [200].…”
Section: Preclinical Studiesmentioning
confidence: 89%
“…The group of Ortega-Pérez L.G. et al [200] prepared Callistemon citrinus leaf extract in phyto-phospholipid complexes aiming to use them (doses range 50-200 mg extract/kg) for weight gain prevention in Wistar rats fed with a hypercaloric diet. They obtained phytosomes with the C. citrinus extract of a small size, high entrapment efficiency, improved oral bioavailability and enhanced stability at 20 • C (over three months) [201,202].…”
Section: Preclinical Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…C. citrinus phytosomes reduced biochemical and morphometrical features in wistar rat fed a heigh-fat diet, even at low dosages. In addition, the results demonstrated that boosting with Callistemon citrinus phytosomes reduced the animals' excessive weight 28 .…”
Section: Phytosomes For the Treatment Of Obesitymentioning
confidence: 94%
“…Every process was shielded from light. One method for increasing the bioavalibility and solubility of plant extract is the use of phytosomes [28] . In the emulsion, the C. citrinus phytosome average particle size of 129.98 nm±18.30 nm.…”
Section: Phytosomes For the Treatment Of Obesitymentioning
confidence: 99%